Adolescent perceptions of orthodontic treatment risks and risk information: A qualitative study. (July 2018) - Perry, John; Johnson, Ilona; Popat, Hashmat; Morgan, Maria Z.; Gill, Paul
Abstract: Introduction: For effective risk communication, clinicians must understand patients' values and beliefs in relation to the risks of treatment. This qualitative study aimed to explore adolescent perceptions of orthodontic treatment risks and risk information. Methods: Five focus groups were carried out with 32 school/college pupils aged 12–18 in Wales, UK. Participants were purposively selected and had all experienced orthodontic treatment. A thematic approach was used for analysis and data collection was completed at the point of data saturation. Results: Four themes emerged from the data; (a) day-to-day risks of orthodontic treatment, (b) important orthodontic risk information, (c) engaging with orthodontic risk information and (d) managing the risks of orthodontic treatment. Day-to-day risks of orthodontic treatment that were affecting participants "here and now" were of most concern. Information about preventing the risks of treatment was deemed to be important. Participants did not actively seek risk information but engaged passively with information from convenient sources. Perceptions of risk susceptibility influenced participants' management of the risks of orthodontic treatment. Conclusions: This study demonstrates that adolescent patients can understand information about the nature and severity of orthodontic treatment risks. However, adolescent patients can have false perceptions if the risks are unfamiliar, perceived only to have a future impact or if seen as easy to control. Adolescent patients must be provided with timely and easily accessible risk information and with practical solutions to prevent the risks of treatment. Clinical significance: The views and experiences gathered in this study can assist clinicians to better understand their young patients' beliefs about treatment risks, facilitate effective risk communication and contribute to improved patient-centred care.